2020
DOI: 10.3390/ijms21186775
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting the Effect of a 3D Microscaffold on the Transcriptome of Neural Stem Cells with Computational Approaches: A Focus on Mechanotransduction

Abstract: 3D cell cultures are becoming more and more important in the field of regenerative medicine due to their ability to mimic the cellular physiological microenvironment. Among the different types of 3D scaffolds, we focus on the Nichoid, a miniaturized scaffold with a structure inspired by the natural staminal niche. The Nichoid can activate cellular responses simply by subjecting the cells to mechanical stimuli. This kind of influence results in different cellular morphology and organization, but the molecular b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(32 citation statements)
references
References 114 publications
5
27
0
Order By: Relevance
“…Indeed, ncRNAs could possibly influence numerous coding genes found altered via RNAseq, thus suggesting an involvement in the altered pathways in mechanotransduction, stemness, and neural differentiation that were investigated via KEGG, REACTOME, and WikiPathways, along with GO analysis. The deregulation of pathways related to membrane alteration (e.g., Axon guidance, Extracellular matrix organization, Focal adhesion) as well as cell-cell interaction (e.g., Tight junction) revealed a role for both lncRNAs and small ncR-NAs in altering expression of coding genes implicated in mechanotransduction, supporting previous studies [32], but also highlighted their importance in biological processes. Noncoding RNAs were also shown to influence metabolic processes of coding genes, resulting in the overall deregulation of metabolic pathways observed.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…Indeed, ncRNAs could possibly influence numerous coding genes found altered via RNAseq, thus suggesting an involvement in the altered pathways in mechanotransduction, stemness, and neural differentiation that were investigated via KEGG, REACTOME, and WikiPathways, along with GO analysis. The deregulation of pathways related to membrane alteration (e.g., Axon guidance, Extracellular matrix organization, Focal adhesion) as well as cell-cell interaction (e.g., Tight junction) revealed a role for both lncRNAs and small ncR-NAs in altering expression of coding genes implicated in mechanotransduction, supporting previous studies [32], but also highlighted their importance in biological processes. Noncoding RNAs were also shown to influence metabolic processes of coding genes, resulting in the overall deregulation of metabolic pathways observed.…”
Section: Discussionsupporting
confidence: 86%
“…Lastly, 130 significant terms from turquoise module and 73 from the blue one emerged in GO CC analysis, and the top 10 are displayed as dotplot graph respectively in Figure 4E,F. Both the up-and down-regulated genes are implicated in terms such as "cellular anatomical entity", "intracellular", "cytoplasm", "membrane", "extracellular region", and "organelle" highlighting the Nichoid ability to transcriptionally deregulate ncRNAs related to multiple cellular levels, integrating what has been previously reported for coding transcripts [32]. Interestingly, only the up-regulated terms appear to be correlated with neuronal-specific phenotypes, such as "neuronal cell body", "synapse", and "somatodendritic compartment" (Figure 4E).…”
Section: Functional Enrichment Analysis Of Genes In Co-interacting Modules Predicts Functions For Non-coding Rnas In Gene Ontologysupporting
confidence: 63%
See 2 more Smart Citations
“…The Nichoid remodels the cytoskeleton and conditions cells to maintain a more spherical shape of the nuclei during proliferation with respect to cells grown on flat substrates [ 28 ]. Furthermore, we demonstrated that this scaffold maintains MSCs multipotency in vitro [ 31 , 32 , 33 ]. The architecture of the Nichoids allows optical inspection being composed of micrometric pores (tens of microns in size) and has a thickness of only 30 μm [ 24 ].…”
Section: Introductionmentioning
confidence: 99%